2014
DOI: 10.1080/07448481.2014.899232
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Human Immunodeficiency Virus Testing and Associated Risk Factors in College Students

Abstract: Objective This study documents the prevalence of HIV testing in a sample of college students and examines associated demographic and behavioral characteristics. Participants College students ages 18 or older were randomly selected to participate in a health behavior survey at a southeastern university in September 2011. Methods Only sexually active students were included (n = 905). Relationships between demographic and sexual behavior characteristics were explored using logistic regression and classificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
3
6
0
1
Order By: Relevance
“…Most of the concern focused on male students who are sexually active (particularly homosexually active), who engage in risky sexual behaviours, and who have inadequate access to individualised HIV prevention counselling and HIV testing on campus. They also have concerns about the potential burden of HIV-positive results which in turn contributes to the low use of HIV testing service [41]. Integrating HIV counselling and testing services into university health care services will help improve the accessibility of HIV services among students and meet the needs of those who are at high risk of HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the concern focused on male students who are sexually active (particularly homosexually active), who engage in risky sexual behaviours, and who have inadequate access to individualised HIV prevention counselling and HIV testing on campus. They also have concerns about the potential burden of HIV-positive results which in turn contributes to the low use of HIV testing service [41]. Integrating HIV counselling and testing services into university health care services will help improve the accessibility of HIV services among students and meet the needs of those who are at high risk of HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Other limitations relate to the response rate and data collection method. While the overall response rate is similar to another e-mailed survey of university students ( Dennison et al, 2014 ), prior research has demonstrated that response rates for in-person surveys on smoking exceed e-mailed ones (91% vs. 24%), and that non-responders are more likely to be current smokers ( Norton et al, 2009 ). This may have been why the percent of current smoking in the sample (8.3%) is somewhat lower than typical college smoking rates ( American College Health Association, 2015a ).…”
Section: Discussionmentioning
confidence: 56%
“…2019;15:e2144. doi: 10.18294/sc.2019.2144 sino también acceden menos a determinados insumos, como la prueba serológica de VIH (36,37,38) . Esto se debe, en parte, a la influencia de los patrones de masculinidad en el bajo reconocimiento del riesgo y en la baja movilización de los heterosexuales frente a la epidemia del VIH desde su surgimiento, lo que hace que, hasta hoy, los hombres heterosexuales no posean redes de apoyo y socialización en las que circule información sobre nuevas tecnologías preventivas (39) .…”
Section: Resultados Y Discusiónunclassified